1995
DOI: 10.1123/jsr.4.3.172
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Adherence to Sport Injury Rehabilitation in College-Age Recreational Athletes

Abstract: The purpose of the present study was to identify factors that contribute to adherent or nonadherent behavior during sport injury rehabilitation programs. Thirty-nine male and female college-age recreational athletes participated. The variables under examination were self-motivation/apathy, perceived exertion, social support, scheduling concerns, the clinical environment, and pain tolerance. Independent t tests (p < .05) were used to determine the difference between the adherer and nonadherer groups on each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 6 publications
3
25
1
Order By: Relevance
“…In another study, adherers to rehabilitation were less concerned with occasional pain compared to those who did not adhere and who reported stopping once they felt pain. 29 In contrast, Pizzari and colleagues found in their interviews that pain had only a fleeting influence upon adherence throughout various stages of the rehabilitation process. 31 Although there has been great variance in the amount of influence pain has on the rehabilitation process, all studies have reported that pain is a contributing factor.…”
Section: Personal Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…In another study, adherers to rehabilitation were less concerned with occasional pain compared to those who did not adhere and who reported stopping once they felt pain. 29 In contrast, Pizzari and colleagues found in their interviews that pain had only a fleeting influence upon adherence throughout various stages of the rehabilitation process. 31 Although there has been great variance in the amount of influence pain has on the rehabilitation process, all studies have reported that pain is a contributing factor.…”
Section: Personal Factorsmentioning
confidence: 99%
“…Other authors have reported that adherers to exercise seemed to make time for their rehabilitation while nonadherers found rehabilitation an inconvenience. 29 Through discriminant analysis, the authors reported that scheduling concerns were the greatest contributor to the overall difference between adherers and nonadherers, specifically nonadherers thought that their sessions required too much time. While the aforementioned studies document "perceived lack of time" as a major barrier to rehabilitation, the implicit conclusion remains that patients who prioritize rehabilitation are more likely to make time to attend sessions, follow instructions, and complete home-based exercises.…”
Section: Personal Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Athletes who were less self-motivated and placed less emphasis on task incentives were more likely to miss scheduled appointments and less likely to adhere to their rehabilitation programme. Fields et al (18) identified that self-motivation contributed to adherent or nonadherent behavior during sport injury rehabilitation programmes. Self-motivated injured athletes were less likely to be deterred by outside factors that may have prevented attending rehabilitation sessions.…”
Section: Personal Investment Theorymentioning
confidence: 99%
“…Personal factors are stable, dispositional characteristics and those associated with adherence are self-motivation (24,14,18), pain tolerance (19,18), and task difficulty (16).…”
Section: Models Of Cognitive Appraisalmentioning
confidence: 99%